3DHOP: 3D Heritage Online Presenter. (November 2015) - Potenziani, Marco; Callieri, Marco; Dellepiane, Matteo; Corsini, Massimiliano; Ponchio, Federico; Scopigno, Roberto
Abstract: 3D Heritage Online Presenter (3DHOP) is a framework for the creation of advanced web-based visual presentations of high-resolution 3D content. 3DHOP has been designed to cope with the specific needs of the Cultural Heritage (CH) field. By using multiresolution encoding, it is able to efficiently stream high-resolution 3D models (such as the sampled models usually employed in CH applications); it provides a series of ready-to-use templates and examples tailored for the presentation of CH artifacts; it interconnects the 3D visualization with the rest of the webpage DOM, making it possible to create integrated presentations schemes (3D + multimedia). In its design and development, we paid particular attention to three factors: easiness of use, smooth learning curve and performances. Thanks to its modular nature and a declarative-like setup, it is easy to learn, configure, and customize at different levels, depending on the programming skills of the user. This allows people with different background to always obtain the required power and flexibility from the framework. 3DHOP is written in JavaScript and it is based on the SpiderGL library, which employs the WebGL subset of HTML5, implementing plugin-free 3D rendering on many web browsers. In this paper we present the capabilities and characteristics of the 3DHOP framework, using different examples based on concrete projects. Abstract : Graphical abstract: Abstract : Highlights: The presentation of a complete framework, already in use by the community. The imperative-style structure of the framework, as an alternative to declarative approaches. The support for the remote rendering of very complex geometries. The open-source policy, with the aim of the creation of a strong community of users.